IMPLEMENTASI TEAMS GAMES TOURNAMENT BERBANTUAN LECTORA UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR IPS SD - Laila Fatmawati (Universitas Ahmad Dahlan, 2014)
The purpose of this classroom aaction research was to describe application of cooperative learning teams games tournament type assisted Lectora to improve motivation and learning outcomes in social studies elementary school. Subject were fourth grade student in SD N Tukangan Yogyakarta. Result found application of the cooperative learning type teams games tournament type assisted Lectora improves motivation and learning outcomes in social studies elementary school.